Implementasi Sumber Daya Perusahaan Cv. Dewi Bulan - Debora Oktaviani; Diana Vimalakirti Chow; Ricky Ricky; Salsabilla Febriatul Husna; Rizni Aulia Qadri; Immanuel Zai (Journal Of Business, Finance, and Economics (JBFE), 2023)
Now the process of developing information technology is very fast, which allows many companies to take advantage of actual information technology to support the company's business agility. CV. Dewi Bulan is a small and medium business that produces incense or incense. The problems faced by CV. Dewi Bulan is an ineffective business method, her business activities are being registered manually, documents regarding sales, production and purchasing of basic materials are being handwritten on a checklist in the company and bookkeeping is done once a month. These documents cannot be obtained at any time. This problem resulted in negligence in carrying out customer orders. The solution to overcome the above problems is to implement Enterprise Resource Planning, where in reality ERP can automate business realization and the company's business steps. ERP implementation requires technology, namely using Odoo version 11.0. This research principle consists of six stages of the research process, namely, iterature study, data collection, data processing, application modeling, system testing and implementation, as well as conclusions and suggestions. The final step in this study was to conduct a review using the UAT questionnaire and a Likert scale to compare the satisfaction levels of Odoo application users. The results of the questionnaire are favored by the "Satisfied" assessment, this proves that the actual business renewal process implemented can be implemented in CV. Dewi Bulan.